Enhancing reading comprehension through metacognitive reading strategies and peer tutoring among year 7 students at a home school centre / Nadiah Halim, Marina Mohd Arif and Kaarthiyainy Supramaniam - Halim, Nadiah; Mohd Arif, Marina; Supramaniam, Kaarthiyainy (Faculty of Education, 2020)
Many students in Malaysia lack proficiency in the English language, from difficulty understanding the meaning of the text to inferring the text. The use of explicit instruction to introduce reading comprehension skills are also rarely employed in the classroom. This study investigated how metacognitive reading strategies and peer tutoring improved Year 7 students’ reading comprehension at a home-school centre. A total of 20 Year 7 students took part in this research, whereby 10 students were placed in the controlled group and 10 students in the experimental group. Students in the experimental group were exposed to 12 weeks of training on metacognitive reading strategies and peer tutoring session. In addition, IGCSE reading comprehension, learning journals and a semi-structured interview were employed to collect data from the experimental group. A paired sample t-test was conducted to analyse the quantitative data of this study whereas document analysis and thematic analysis were used to analyse the qualitative data. The results obtained from this study indicated that metacognitive reading strategies have assisted students to use suitable techniques to comprehend the reading text and answer the reading comprehension questions. In addition, peer tutoring aids student by having their peers translate meaning of the texts in their native language, explain how to properly use the metacognitive reading skills as well as provide guidance and support in the classroom. Therefore, the findings of this study are significant as it suggests the difficulty of students to adapt to new strategies in a short time; hence, they should be exposed at primary level.